STRATEGI MARKETING KUSUMA KENCANA DALAM MENINGKATKAN PENJUALAN JASA WEDDING ORGANIZER MELALUI SOSIAL MEDIA TIK TOK - Widya Indriati, Kadga (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
AbstractTikTok is a digital platform founded by ByteDance in 2016 in China. The development of TikTok is increasing from year to year. In fact, TikTok is the most downloaded non-gaming application in 2020. This popularity has indirectly made many content creators give birth to various unique ideas, one of which is Kusuma Kencana, a content creator who consistently presents informational content for the services he founded, namely the wedding organizer. By using a qualitative method, this research presents results based on observation, interviews with Faisal and Tim, and documentation. Based on these results, it can be concluded that Kusuma Kencana used a marketing strategy to increase sales of TikTok's social media wedding organizer services, which is the result of observations about showing that marketing strategy. And from the results of these observations, using the Kusuma Kencana Marketing strategy in Increasing Sales of Wedding Organizer Services Through Social Media TikTok which contains Kusuma Kencana's marketing activities, utilizes social media as a medium used in marketing services and promoting its services to customers. A marketing strategy with 7p and STP can be a solution for wedding organizer services. Promotion through several media such as Instagram, TikTok and WhatsApp, Sales Promotion implements promotion through the media social media, Public Relations influencing consumers through interesting content and working with models or celebrities, Personal Sales direct communication between the owner and the bride and groom, Direct Marketing social media as a place to share interesting and creative content to attract the attention of the bride and groom.